Atorvastatin reduces T‐cell activation and exhaustion among HIV‐infected cART‐treated suboptimal immune responders in Uganda: a randomised crossover placebo‐controlled trial. Issue 3 (6th January 2015) - Nakanjako, Damalie; Ssinabulya, Isaac; Nabatanzi, Rose; Bayigga, Lois; Kiragga, Agnes; Joloba, Moses; Kaleebu, Pontiano; Kambugu, Andrew D.; Kamya, Moses R.; Sekaly, Rafick; Elliott, Alison; Mayanja‐Kizza, Harriet
Abstract Objective T‐cell activation independently predicts mortality, poor immune recovery and non‐AIDS illnesses during combination antiretroviral therapy (cART). Atorvastatin showed anti‐immune activation effects among HIV‐infected cART‐naïve individuals. We investigated whether adjunct atorvastatin therapy reduces T‐cell activation among cART‐treated adults with suboptimal immune recovery. Methods A randomised double‐blind placebo‐controlled crossover trial, of atorvastatin 80 mg daily vs. placebo for 12 weeks, was conducted among individuals with CD4 increase <295 cells/μl after seven years of suppressive cART. Change in T‐cell activation (CD3 + CD4 + /CD8 + CD38 + HLADR+) and in T‐cell exhaustion (CD3 + CD4 + /CD8 + PD1 + ) was measured using flow cytometry. Results Thirty patients were randomised, 15 to each arm. Atorvastatin resulted in a 28% greater reduction in CD4 T‐cell activation (60% reduction) than placebo (32% reduction); P = 0.001. Atorvastatin also resulted in a 35% greater reduction in CD8‐T‐cell activation than placebo (49% vs. 14%, P = 0.0009), CD4 T‐cell exhaustion (27% vs. 17% in placebo), P = 0.001 and CD8 T‐cell exhaustion (27% vs. 16%), P = 0.004. There was no carry‐over/period effect. Expected adverse events were comparable in both groups, and no serious adverse events were reported. Conclusion Atorvastatin reduced T‐cell immune activation and exhaustion among cART‐treated adults in a Ugandan cohort. Atorvastatin adjunct therapy should be explored as a strategy to improve HIV treatment outcomes among people living with HIV in sub‐Saharan Africa.